1978
DOI: 10.1079/bjn19780017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold exposure on digestion, microbial synthesis and nitrogen transformations in sheep

Abstract: 1. Six closely shorn sheep were given brome grass (Bromus inermis) pellets at the rate of 59 or 98 g dry matter (dm)/h and maintained at ambient temperatures of 2–5° and 22–25° for 35 d. Measurements of digestion, rate of passage of digesta, and nitrogen transformations were made during the last 13 d of temperature exposure.2. Cold exposure at the lower level of intake reduced the apparent digestibility of dm and organic matter (om) approximately 0.055 units. Apparent digestibility of dm and om was further dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(71 citation statements)
references
References 19 publications
4
64
1
Order By: Relevance
“…Similar results were observed in sheep fed fresh PL and OR diets (Sano et al 2002). The tendency toward reduced BW during cold exposure may mainly be due to reduced digestibilities and water intake and enhanced energy expenditure (Kennedy et al 1976;Kennedy & Milligan 1978;Tsuda et al 1984) because feed intake was the same in both environments. Crude protein intake was estimated to be similar between the PL and OR diets (Tables 1 and 2).…”
Section: Resultssupporting
confidence: 74%
“…Similar results were observed in sheep fed fresh PL and OR diets (Sano et al 2002). The tendency toward reduced BW during cold exposure may mainly be due to reduced digestibilities and water intake and enhanced energy expenditure (Kennedy et al 1976;Kennedy & Milligan 1978;Tsuda et al 1984) because feed intake was the same in both environments. Crude protein intake was estimated to be similar between the PL and OR diets (Tables 1 and 2).…”
Section: Resultssupporting
confidence: 74%
“…This complexity is further increased by changes in C and k with time after feeding because of decreasing particle size with progressive digestion and changes in saliva flow. Compartment B may serve as a transport or shuttle compartment between A and C (Czerkawski, 1984 (Kennedy et al, 1976 ;Kennedy and Milligan, 1978 ;Harrison et al, 1975) (fig. 2) (Faichney and Griffiths, 1978 Zinn and Owens (1983).…”
Section: The Presence Of Protozoamentioning
confidence: 99%
“…The present study with ad libitum-fed sheep showed that there were increases (P < 0.05) of rates of duodenal passage of DM, CP, OM, AA and microbial protein in the cold, compared to a thermoneutral environment. Although similar results have been reported for animals on restricted intakes (Kennedy and Milligan 1978;Kelly et al 1989), this is the first comprehensive study of this type in ad libitum fed sheep. The increased passage of nutrients into the small intestine is presumably related to enhanced forestomach motility (Titchen 1968;Christensen et al 1991;Miaron and Christopherson 1992), but it may also be secondary to increased feed intake induced by the energy demand of the environment.…”
Section: Effects Of Temperaturementioning
confidence: 56%
“…An enhanced digesta flow often improves synthetic efficiency of ruminal bacteria (Kennedy et al 1976;Kennedy and Milligan 1978;Mathison et al 1995). Indeed, the increased (P < 0.05) quantitative contributions of microbial protein to the duodenal AA supply was realized by higher digesta flow induced by cold exposure in the present study.…”
Section: Effects Of Temperaturementioning
confidence: 99%